2008
DOI: 10.1309/ajcpo31thgveuidh
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of a Panel of Tumor Cell Markers During Malignant Progression in Barrett Esophagus

Abstract: Histopathologic grading of dysplasia in Barrett esophagus (BE) shows substantial interobserver and intraobserver variation. We used immunohistochemical analysis with a set of tumor cell markers, ie, epidermal growth factor receptor (EGFR), ERBB2 (HER2/neu), MYC, CDKN2A (p16), SMAD4, MET, CCND1 (cyclin D1), CTNNB1 (beta-catenin), and TP53 (p53), in histologic sections of endoscopic biopsies of 86 patients with BE in various stages of neoplastic progression. The markers, except SMAD4, were scored as 0 (<1% of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…46 β-catenin, which was reduced at the mRNA level in this study, has a pattern of progressive loss of membranous protein expression with, in some studies, an increase in nuclear accumulation. [47][48][49][50][51][52] Variable findings have been reported for EGFR (epidermal growth factor receptor) expression 53 or amplification, 54 but the progressive reduction in EGFR expression in this study, together with the failure to identify significant differences in EGFR protein expression in normal, BE and EAC tissues in another study, 47 raise doubts regarding the applicability of EGFR-targeted therapy for this cancer type. 55 Another monoclonal antibody target, HER-2/erbB-2, was the most stably expressed gene in this study, with very similar mRNA levels in normal, BE and EAC tissues.…”
Section: Discussionmentioning
confidence: 81%
“…46 β-catenin, which was reduced at the mRNA level in this study, has a pattern of progressive loss of membranous protein expression with, in some studies, an increase in nuclear accumulation. [47][48][49][50][51][52] Variable findings have been reported for EGFR (epidermal growth factor receptor) expression 53 or amplification, 54 but the progressive reduction in EGFR expression in this study, together with the failure to identify significant differences in EGFR protein expression in normal, BE and EAC tissues in another study, 47 raise doubts regarding the applicability of EGFR-targeted therapy for this cancer type. 55 Another monoclonal antibody target, HER-2/erbB-2, was the most stably expressed gene in this study, with very similar mRNA levels in normal, BE and EAC tissues.…”
Section: Discussionmentioning
confidence: 81%
“…108 Immunostaining for α-methylacyl-CoA racemase (AMACR) and for a panel of biomarkers that includes β-catenin, cyclin D1, and p53 also has shown promise in preliminary studies for distinguishing dysplasia from reactive changes and for distinguishing among grades of dysplasia. 109111 In contrast to those promising reports, a study that attempted to correlate grades of dysplasia with messenger RNA expression levels for a panel of 10 genes believed to contribute to carcinogenesis in Barrett's esophagus found that the utility of the panel was severely limited by significant interpatient and intrapatient variations in gene expression levels. 112 At this time, data supporting the use of biomarkers to confirm the histologic diagnosis of dysplasia must be considered preliminary, and biomarkers cannot yet be recommended for this purpose for routine clinical practice.…”
Section: Agai Procedures For Construction Of Technical Reviewsmentioning
confidence: 95%
“…Immunohistochemistry for p53 and Ki67 has also been reported to correlate with the severity of dysplasia in assessing Barrett's biopsies [133, 134]. In another study of 86 biopsies, protein overexpression of β -catenin helped diagnose LGD, whereas overexpression of cyclin D1 and p53 discriminated HGD from LGD [135]. However, most pathologists rely on routine stains and morphology to diagnose and grade dysplasia and immunohistochemistry is rarely, if ever, used in routine day-to-day practice in most centers.…”
Section: Histopathology Diagnosis and Dysplasia Gradingmentioning
confidence: 99%